2020
DOI: 10.1155/2020/8856260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatments on the Content of Bioactive Substances and Antioxidant Properties of Sweet Potato (Ipomoea batatas L.) Tubers

Abstract: Heat treatment can affect the bioactive compounds in sweet potato (SP). In this work, we monitored the influence of heat treatment (boiling, steaming, microwaving, and baking) on the total polyphenols content (TPC), total antioxidant capacity (TAC), total anthocyanins content (TANTC), and phenolics acids (chlorogenic (CGA), neochlorogenic (neo-CGA), and trans-ferulic (tFA)) in two SP varieties grown in Slovakia and Croatia. TPC, TAC, and TANT were determined spectrophotometrically and phenolic acids by HPLC. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Boiling was shown to have the most detrimental effect: it lowered the levels of chlorogenic acid by 29% (in the 414-purple variety from Slovakia), neochlorogenic acid by 69% (in the 414-purple variety from Croatia), and trans-ferulic acid by 29% (in the Beauregard variety from Croatia). In contrast, all these treatments increased the levels of total polyphenols, total anthocyanins, and total antioxidant activity, mostly in all analyzed samples [ 67 ].…”
Section: Food-processing Techniques and Their Effects On Polyphenols Content And Bioavailabilitymentioning
confidence: 99%
“…Boiling was shown to have the most detrimental effect: it lowered the levels of chlorogenic acid by 29% (in the 414-purple variety from Slovakia), neochlorogenic acid by 69% (in the 414-purple variety from Croatia), and trans-ferulic acid by 29% (in the Beauregard variety from Croatia). In contrast, all these treatments increased the levels of total polyphenols, total anthocyanins, and total antioxidant activity, mostly in all analyzed samples [ 67 ].…”
Section: Food-processing Techniques and Their Effects On Polyphenols Content And Bioavailabilitymentioning
confidence: 99%
“…Other researchers who worked on OFSP and PFSP grown in Croatia and Slovakia observed a similar trend where the total phenolic content in all heat-treated samples, except boiling, were higher compared to the raw samples [ 118 ]. Losses of up to 39% occurred in boiled samples.…”
Section: Effects Of Postharvest Processing and Cooking On Sweetpotato Bioactive Compoundsmentioning
confidence: 56%
“…Losses of up to 39% occurred in boiled samples. The general increase in phenolics in cooked samples was attributed to the release of bound phenolics during cooking [ 118 ]. On the contrary, in a study conducted in Brazil, researchers observed an increase in phenolic compounds content after boiling in two of their four biofortified sweetpotato varieties, and a decrease in the other two [ 119 ].…”
Section: Effects Of Postharvest Processing and Cooking On Sweetpotato Bioactive Compoundsmentioning
confidence: 99%
See 2 more Smart Citations